Adultery and the Gaze : a Reading of Tornabuoni’s 'Story of Devout Susanna' - Gabrielli, Francesca Maria (2010)
One of the main aspects of Lucrezia Tornabuoni’s Istoria della casta Susanna is the narrative insistence on the reifying effects of a gaze gendered as male: Susanna is, as in the apocryphal/deuterocanonical pre-text (see Glancy), represented as the passive object of voyeurism. Tornabuoni’s sacred narrative includes in the representation of Susanna a series of allusions to Dante’s Beatrice (Pg XXX, XXXI), Petrarch’s Laura (RVF 126) and Ovid’s Proserpina (Met. 5.341-661). Carrying the plurivocal traces of other female figures represented as visual objects, Tornabuoni’s depiction of Susanna suggests how the objectifying effects of scopophilia can slide from exaltation to abasement, from love to rape. In its final part, the sacred narrative opens up to another account of an allegedly adulterous woman (Jn 7:53-8:11). By means of this intertextual inclusion the verbal texture of Tornabuoni’s Susanna operates to ultimately and radically subvert the potentially dangerous logic inherent in the representation of a woman as to-be-looked-at-ness.
Projekt MZOS
ENG